2022
DOI: 10.1088/1742-6596/2265/2/022022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Turbulent Time Scales on Wake Recovery and Operation

Abstract: Enhancing wake recovery behind wind turbines has the potential to significantly improve the power production and efficiency of large wind farms. Rather than investigating turbine control strategies, floater motion or global turbulent quantities such as turbulence intensity, this work aims to study wake stability and recovery through a focus on the turbulent scales of the inflow. Using Large Eddy Simulations of a single turbine, sinusoidal streamwise forcing is applied to the inflow with a constant amplitude an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Whereas tip vortices hinder the transport of momentum to the inner core of the wake (Lignarolo et al 2015), large wake structures, like coherent meandering, can enhance the transport. Frederik et al (2020), Korb et al (2023) and Hodgson et al (2023) have shown that periodic excitation of the wake can lead to faster recovery. The different studies found an optimum excitation frequency around St ≈ 0.3, similar to our results.…”
Section: Discussion About Enhanced Recovery and The Nonlinear Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas tip vortices hinder the transport of momentum to the inner core of the wake (Lignarolo et al 2015), large wake structures, like coherent meandering, can enhance the transport. Frederik et al (2020), Korb et al (2023) and Hodgson et al (2023) have shown that periodic excitation of the wake can lead to faster recovery. The different studies found an optimum excitation frequency around St ≈ 0.3, similar to our results.…”
Section: Discussion About Enhanced Recovery and The Nonlinear Dynamicsmentioning
confidence: 99%
“…(2023) and Hodgson et al. (2023) have shown that periodic excitation of the wake can lead to faster recovery. The different studies found an optimum excitation frequency around , similar to our results.…”
Section: Transition-region Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 using the same finitevolume solver as for the URANS simulations, although in a three-dimensional version instead, EllipSys3D [12]. The LES setup is the same as was used in a recent cross-code study by Hodgson et al (2023) [13] and details about the numerical setup can be found there. One difference in the setup is however that a slightly different grid is used: The domain size is L x × L y × L z = 2.56 km×2.56 km×1.0 km with horizontal grid spacing ∆x = ∆y = 10 m, while the vertical grid spacing is the same as in the URANS.…”
Section: Numerical Solver and Setupmentioning
confidence: 99%
“…Large-Eddy Simulations (LES) capture unsteadiness, a wide range of turbulence scales and energy fluxes, thereby providing a more detailed description of the instantaneous flow field than RANS and catching the interaction between atmosphere and wind farm, especially in buoyancy-driven flows [25,26]. Previous studies have shown changes to the dynamical inflow due to induction [30,31], and changes in amplitudes and turbulent length scales can potentially affect the wake development [32]. Yet, with blockage being driven mainly by the mean flow characteristics, it is expected to be accurately quantified with well-conducted RANS simulations.…”
Section: Introductionmentioning
confidence: 99%